Customer Satisfaction Without Loyalty: Exploring Behavioral Switching Factors - Nurul Ittaqullah (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
Customer satisfaction has long been considered one of the primary predictors of customer loyalty in marketing literature. However, contemporary consumer markets demonstrate that satisfied consumers do not always remain loyal to brands. The increasing availability of alternatives, digital exposure, aggressive promotional activities, and dynamic consumer preferences have contributed to a growing phenomenon known as the satisfaction–loyalty gap. This study aims to explore behavioral switching factors that explain why satisfied consumers still switch brands despite positive consumption experiences. The study employs a qualitative literature review approach by synthesizing previous studies related to customer satisfaction, customer loyalty, switching behavior, and consumer behavior. The findings indicate that behavioral switching factors are multidimensional and involve psychological, economic, emotional, and situational mechanisms. The dominant factors identified include variety-seeking behavior, price sensitivity, promotional attractiveness, low switching costs, weak emotional attachment, social influence, and digital consumer environments. The study suggests that customer satisfaction alone is insufficient to ensure long-term loyalty in highly competitive markets. Companies therefore need to develop stronger emotional engagement, relational strategies, and customer experiences beyond merely achieving functional satisfaction.